The Role Of Your Market Based On Creative Economics In Improving Community Welfare According To The Islamic Perspective Economics - Tria Silvia; Zuhrinal M Nawawi; Nurul Jannah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Objective Study This is For know Role Market You based economy creative in improving community welfare from an Islamic economic perspective in Deli Serdang. This research use approach qualitative descriptive. Sample study This as much 7 person covers manager, trader And visitors in market You. Results study This find that Market You is something place Which showing results economy creative Which in manage by This local community aims to improve welfare and economic growth village communities through the development of their creative economic efforts. Your market plays a big role important to development economy creative, Good in matter activity economy public, creation of jobs, community income and sustainability of socio-economic life public Village Trail Long, Regency Deli Serdang To use For increase well-being public.